The Rate of Success of CPR in Patients Suffering from Cardiac Arrest in Patients Admitted in CCU in Cardiology Department Ayub Medical Teaching Institute : Rate of Success of CPR in Patients Suffering from Cardiac Arrest - Fawad Gul, Sardar; Khan, Muhammad Imran; Shah, Yasir Ali; Khan, Zia Ullah; Jawad Gul, Sardar; Basre, Rabia (Pakistan Journal of Health Sciences, 2024)
Cardiopulmonary resuscitation (CPR) is an essential procedure used to treat patients who are in cardiac arrest, particularly in the Critical Care Unit (CCU). Objective: To assess the success rate of CPR admitted to the CCU, revealing insight on the effectiveness of current resuscitation techniques. Methods: This retrospective study was conducted at Department of Cardiology Ayub Medical Teaching Institute, Abbottabad, between 13th April 2023 to 30th November 2023, 110 patients had cardiac arrest while in the intensive care unit. Data were gathered and examined on patient demographics, pre-existing comorbidities, time to start CPR, duration of CPR, and results. CPR success was defined as a sustained restoration of spontaneous circulation (ROSC) for at least 20 minutes. Results: This study included 110 cardiac patients. Most patients (68.18%) were male. Hypertension was the most common comorbidity at 72.7%. CPR started on average 4.8 minutes late, with a 1.2-minute standard deviation. The average CPR time was 18.2 minutes, with a 5.6-minute SD. After cardiac arrest, 60 (54.5%) patients began CPR within 5 minutes. Another subgroup found 96.0% CPR success in 25 (22.7%) ventricular fibrillation patients. Then occurred ventricular tachycardia (80.0%), pulseless electrical activity (76.0%), and asystole (68.9%). These data suggest that CPR works better in ventricular fibrillation patients. Conclusions: This research sheds light on cardiac arrest CCU patients’ demographics, care, and outcomes. The data show that early CPR and ventricular fibrillation detection and treatment improve outcomes for these individuals.